Routine and quality management in the chemical industry - Vieira, Felipe Martins; Fontes, Selma Velozo; Silva, Paulo Vitor Jordão da Gama (Seven Editora, 2023)
The work shows the importance of routine management, performance, and quality in chemical industry companies. To this end, the necessary factors for application are described, in addition to showing better results when routine management is used. In this study, successful cases were used and a breakdown of the main indicators was exposed. The main results were the reduction of maintenance cost of physical and chemical analysis equipment, the reuse of organic waste, the resolution of failures in the production plant, the control of production procedures, and the resolution of failures in the pulp and paper industry.DOI: https://doi.org/10.56238/devopinterscie-045